2018
DOI: 10.1080/13557858.2017.1418298
|View full text |Cite
|
Sign up to set email alerts
|

‘Simple and easy:’ providers’ and latinos’ perceptions of the fecal immunochemical test (FIT) for colorectal cancer screening

Abstract: Despite the increasing acceptance of the FIT among the health care community, a significant lag time still exists among our study's populations. Study findings speak to novelty of the FIT test among underserved populations and the health disparity gap between health innovations/discoveries. Increased awareness and education efforts about the efficacy coupled with information about its accessibility, ease, and user instructions may increase the adoption of FIT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 36 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…Likewise to female sex, individuals with previous experience of faecal sampling were more likely to experience higher anxiety levels related to their screening decision. Even if collecting a faecal test sometimes is associated with unpleasantness,26 embarrassment26 27 and concerns about hygiene and contamination,27 it is in general well accepted 28 29. That said, there might be another explanation to this association than the experience of faecal sampling itself.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise to female sex, individuals with previous experience of faecal sampling were more likely to experience higher anxiety levels related to their screening decision. Even if collecting a faecal test sometimes is associated with unpleasantness,26 embarrassment26 27 and concerns about hygiene and contamination,27 it is in general well accepted 28 29. That said, there might be another explanation to this association than the experience of faecal sampling itself.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 48 papers were included in this review of the literature. A flow chart of the study selection process is reported in Figure 1 11–58 …”
Section: Resultsmentioning
confidence: 99%
“…Further economic barriers to FOBT based screening included the need for financial support to complete the screening process and taking unpaid time off work 12,13,20–22,27,29–31,52 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Translation of materials would have been insufficient; therefore, it was necessary to “transcreate” (formative research + translation + cultural adaptation) the materials for a new audience. The content of the Latinos CARES intervention was informed by a series of focus groups that examined Latinos' awareness, knowledge, and perceptions about CRC screening and the feasibility of FIT adoption ( Aguado Loi et al, 2018 ).…”
Section: Implementation and Results: Three Cancer Education Exemplarsmentioning
confidence: 99%